Formulation and evaluation of stimuli-sensitive hydrogels of timolol maleate and brimonidine tartrate for the treatment of glaucoma - Dubey, Akhilesh; Prabhu, Prabhakara (International Journal of Pharmaceutical Investigation)
Background: Stimuli-sensitive hydrogels are hydrophilic, three-dimensional, polymeric network structure capable of imbibing large amounts of water or biological fl uids on stimulation, such as pH, temperature, and ionic change. Owing to the drawback of conventional therapy for ocular delivery, and to provide additive effect on intraocular pressure (IOP) reduction, stimuli sensitive hydrogel membranes containing a combination of timolol maleate and brimonidine tartrate were formulated for the treatment of glaucoma. Materials and Methods: Stimuli-sensitive hydrogel were formulated by timolol maleate and brimonidine tartrate. Poly acrylic acid (carbopol C 934p) is used as a gelling agent, hydroxylpropyl methylcellulose as viscolizer, sodium chloride as tonicity agent. Bezalkonium chloride as preservative. White rabbits of both sexes, weighing between 2 and 3 kg were used for the study. Stirring of ingredients in pH 4 phosphate buffers at high speed was carried out. Results: Viscosity of the prepared hydrogels lies in the optimum range that is, 25-55 cps. Infrared spectroscopy studies show that there is no interaction between the drug and polymer. Drug released up to 90% at the end of 8 h. The hydrogel membranes were found to be sterile, nonirritant to the eye. Marketed formulation showed a decrease in IOP up to 14 mmHg at the end of 5 h and then elimination of drug, F2 and F6 maintain the sustained effect up to 12 h. Conclusion: Stimuli-sensitive hydrogels was successfully formulated and evaluated for rheological studies, drug release studies, drug interaction studies, sterility studies, ocular irritation studies, and in vivo studies. IOP lowering activity of the combination of timolol maleate and brimonidine tartrate in stimuli-sensitive hydrogel was better when compared with alone medication, which shows the additive effect of combination medication.
Keywords: Brimonidine tartrate; carbopol; intraocular pressure; stimuli-sensitive hydrogel; timolol maleate